Factors influencing the uptake of HIV counselling and testing (HCT) service : the case of the employees of the Namibian Correctional Service at Elizabeth Nepemba Correctional Facility - Velikoshi, Tangeni Immanuel Ndawedwa Oyehetupe (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.